(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background To administer general anaesthesia with controlled ventilation, laryngoscopy and endotracheal intubation is necessary.Suxamethonium is drug of choice but some side effects preclude its use. Pretreatment with Magnesium sulphate reduces suxamethonium induced complications. Objective To see the effects of pretreatment with magnesium sulphate on suxamethonium induced complications during induction of general anaesthesia. Methods A total number of sixty patients of ASA grade I and II were selected randomly as per inclusions and exclusions criteria , thirty in each group. Group- C is the control group and group-M-patients were received magnesium sulphate 60mg per kg. Pulse rate, blood pressure, SPO2, ECG, Serum K+ concentration, fasciculation, myalgia and side effects of magnesium sulphate were recorded. Results Suxamethnium induced complications like fasciculation, raised potassium concentration, haemodynamic change during intubation and post operative myalgia significantly reduced in patients pre treated with magnesium sulphate. Conclusion Pretreatment with magnesium sulphate reduces incidence of suxamethonium induced complications during induction of general anaesthesia. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19813 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 27-32